Development of Cadra cautella Walker (Lepidoptera: Pyralidae) on Peanuts, Almonds, and Cashews - Rahayu, Fitria Ariani; Astuti, Ludji Pantja; Rizali, Akhmad (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2023)
Cadra cautella Walker pest (Lepidoptera: Pyralidae) is a group of significant pests that can attack various stored products. The presence of C. cautella can cause damage to stored products, i.e. holes, contamination, and weight loss of stored products. This study aimed to determine the development time and life cycle of C. cautella in peanuts, almonds, and cashews. This research consisted of three diets repeated ten times and arranged in a Completely Randomized Design. This research carried out by preparing 30 eggs (0–24 h old) in each insect diet. The observed variables consist of the development of each phase (eggs, I-V instar larvae, prepupae pupae, adult), life cycle, longevity, fecundity, and fertility. The result showed that the diet type significantly affected the development of C. cautella. The developmental time and life cycle of C. cautella on cashews was shorter than on peanuts and almonds. Furthermore, the fecundity and fertility of C. cautella on cashews was higher than on peanuts and almonds. The results showed that cashews were of the suitable diets for the development of C. cautella.